Co-Construcción Soluciones Barriales Participativas, Caso de Estudio: Barrio “Santo Domingo de Guzmán” Cantón Catamayo Período Noviembre 2021 Febrero 2022. - Cuncay Cuncay, Soraya Alejandra (2022)
The neighborhood organization constitutes a space of constant union among the people who live in a community to work for its development and progress. That is why this research work has had the purpose of contributing to the Santo Domingo de Guzmán neighborhood of Catamayo Canton, Province of Loja, in the construction of effective solutions, applying participatory, independent and democratic processes oriented to meet citizen demands, carried out through three specific objectives: to promote the organization and participation in the neighborhood, to assist organizations in the development of collective diagnoses and to support the design of solutions to the problems identified. We worked with 73 people between 18 and 64 years of age, in different meetings, participatory workshops with children from 7 years of age and adolescents from 14 to 15 years of age; we applied a structured interview for the directors and a survey directed to the heads of household or members of the family nucleus aged 18 or older. It was found that 81% of the residents identified the lack of infrastructure, equipment and other existing problems, but there are people who were unaware of this situation and this is due to the short time they have been in the neighborhood. Another important point that was verified by means of the observation sheet was the lack of respect for the environment, generated by: fumes and garbage discarded in vacant lots, which causes bad odors and attracts insects and other animals, evidencing the bad appearance of the neighborhood; therefore, it is important to continue developing projects that allow addressing the needs of the citizens and thus strengthen and encourage practices of neighborhood organization and participation to give way to the construction of neighborhood solutions.